Penerapan Kombinasi Algoritma Caesar Cipher pada Block Acak dan Cipher Transposisi Dalam Mengamankan Pesan - mahmuda saputra; Alva Hendi Muhammad (Institut Shanti Bhuana, 2021)
The developments in technology for using security of information are still a threat to every party in processing and transaction confidentiality of messages sent received by users. In this study, the authors carried out a process of learning in terms of classical security with a Caesarean algorithm model with technical support for random blocks of messages and the use of ciphertexts in password transposition. This is to see how the flow can be controlled in describing a message to be conveyed to the required destination. This process is invincible with a few simple experiments, in order to achieve the desired results. Some of the research results carried out in this study include (1) the existence of a process in using the Caesarean cipher cryptographic algorithm, (2) For learning in an information or message that will be sent every time it is received, (3) Each stage of the Caesarean Cipher algorithm is very useful for exploring a messages with a more secure yahoo combination. (4) Can carry out a combination process with random block techniques and transposition ciphers.